Association between trunk muscles characteristics with lower limb injuries: A systematic review. (July 2018) - Emami, M.; Mohseni Bandpei, M.A.; Rahmani, N.; Biglarian, A.; Taghipour, M.
Highlights: Lower limb injuries are the majority of sport injuries in sports involve running and jumping. The aim of this study was to review studies conducted on the association between stabilizer muscles characteristics with lower limb injuries. The results of reviewed studies indicate that size, endurance, strength and activity of stabilizer muscles are related to lower limb injuries. Further research is needed to support the findings of this study and to assess the effect of stabilization exercises to reduce the rate of injuries.